2016
DOI: 10.1164/rccm.201511-2234oc
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Mortality and Hospital Costs Associated with Surviving Intensive Care

Abstract: Rationale: Survivors of critical illness experience significant morbidity, but the impact of surviving the intensive care unit (ICU) has not been quantified comprehensively at a population level.Objectives: To identify factors associated with increased hospital resource use and to ascertain whether ICU admission was associated with increased mortality and resource use.Methods: Matched cohort study and pre/post-analysis using national linked data registries with complete population coverage. The population cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
155
1
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(188 citation statements)
references
References 40 publications
(31 reference statements)
10
155
1
7
Order By: Relevance
“…However, we could match patients on important markers of illness severity including mechanical ventilation, vasopressor use and organ failure. Although both illness severity and pre-morbid patient characteristics are important for patient outcomes (26, 27), recent data indicate that admission diagnosis and illness severity score become less important for patient outcomes than pre-morbid patient characteristics after a prolonged ICU stay, which is a major reason we included ICU LOS in the propensity match model (28). Most patients in the matched CIPNM and non-CIPNM groups had an ICU LOS longer than 10 days, which is the transition point at which admission diagnosis and illness severity no longer predict outcome better than pre-ICU baseline patient characteristics (which were included in our model).…”
Section: Discussionmentioning
confidence: 99%
“…However, we could match patients on important markers of illness severity including mechanical ventilation, vasopressor use and organ failure. Although both illness severity and pre-morbid patient characteristics are important for patient outcomes (26, 27), recent data indicate that admission diagnosis and illness severity score become less important for patient outcomes than pre-morbid patient characteristics after a prolonged ICU stay, which is a major reason we included ICU LOS in the propensity match model (28). Most patients in the matched CIPNM and non-CIPNM groups had an ICU LOS longer than 10 days, which is the transition point at which admission diagnosis and illness severity no longer predict outcome better than pre-ICU baseline patient characteristics (which were included in our model).…”
Section: Discussionmentioning
confidence: 99%
“…These were a measure of multimorbidity (completed by patients), the Functional Comorbidity Index (FCI),21 to quantify the burden of comorbidity for each patient, and a measure of caregiver strain (completed by caregivers), the Modified Caregiver Strain Index (MCSI) 22. These were included because comorbidity burden is associated with readmissions,14 and caregiver strain and psychological morbidity have been highlighted as prevalent among ICU survivors’ carers 7…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported that 25% of ICU survivors in Scotland experienced unplanned rehospitalisation within 90 days of hospital discharge,14 a rate comparable with conditions such as heart failure, chronic respiratory disease and pneumonia 15 16. Early rehospitalisation is a widely used healthcare quality indicator that is linked to financial penalisation in some healthcare systems 17.…”
Section: Introductionmentioning
confidence: 99%
“…Limited bed capacity in ICUs results in cancelled urgent operations and in non-clinical transfers to other such units 4. Given that intensive care is an expensive resource with healthcare costs for survivors that commonly extend well beyond admission,5 this trend is unlikely to be sustainable. Crucially, for patients with chronic disease and established frailty, undergoing the burden of a prolonged stay in intensive care for an acute illness may not deliver sustainable benefit,56 with the important caveat that the definition of “benefit” is a very individual thing.…”
mentioning
confidence: 99%